Total Synthesis of Taxol Enabled by Inter‐ and Intramolecular Radical Coupling Reactions. Issue 10 (1st February 2023) - Imamura, Yusuke; Takaoka, Kyohei; Komori, Yuma; Nagatomo, Masanori; Inoue, Masayuki
Abstract: Taxol is a clinically used drug for the treatment of various types of cancers. Its 6/8/6/4‐membered ring (ABCD‐ring) system is substituted by eight oxygen functional groups and flanked by four acyl groups, including a β‐amino acid side chain. Here we report a 34‐step total synthesis of this unusually oxygenated and intricately fused structure. Inter‐ and intramolecular radical coupling reactions connected the A‐ and C‐ring fragments and cyclized the B‐ring, respectively. Functional groups of the A‐ and C‐rings were then efficiently decorated by employing newly developed chemo‐, regio‐, and stereoselective reactions. Finally, construction of the D‐ring and conjugation with the β‐amino acid delivered taxol. The powerful coupling reactions and functional group manipulations implemented in the present synthesis provide new valuable information for designing multistep target‐oriented syntheses of diverse bioactive natural products. Abstract : Taxol, an anticancer drug, possesses an unusually oxygenated and intricately fused 6/8/6/4‐membered ring (ABCD‐ring) structure. Here we report a 34‐step total synthesis of taxol. Inter‐ and intramolecular radical coupling reactions allowed for connection of the A‐ and C‐rings and cyclization of the B‐ring, respectively. The ABC‐ring was then converted to the target by newly devised functional and protective group manipulations.